2016
DOI: 10.1371/journal.pone.0151846
|View full text |Cite
|
Sign up to set email alerts
|

Trial-Based Cost-Utility Analysis of Icotinib versus Gefitinib as Second-Line Therapy for Advanced Non-Small Cell Lung Cancer in China

Abstract: BackgroundOur objective is to compare the cost-utility of icotinib and gefitinib for the second-line treatment of advanced non-small cell lung cancer (NSCLC) from the perspective of the Chinese healthcare system.MethodsModel technology was applied to assess the data of randomized clinical trials and the direct medical costs from the perspective of the Chinese healthcare system. Five-year quality-adjusted life years (QALYs) and incremental cost-utility ratios (ICURs) were calculated. One-way and probabilistic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…One plausible explanation for this finding is that the cost per cycle of the icotinib strategy was lower than that of the pemetrexed maintenance and gefitinib strategies. One recently published study of second-line treatment for advanced NSCLC showed 5-year QALYs of 0.279 and 0.269 and medical costs of $10,662.82 and $13,127.57 in the icotinib and gefitinib groups, respectively, suggesting that icotinib was a less expensive strategy than gefitinib [18]. Consistent with our study, that previous study also found that the utility of PFS was a sensitive parameter.…”
Section: Discussionsupporting
confidence: 91%
“…One plausible explanation for this finding is that the cost per cycle of the icotinib strategy was lower than that of the pemetrexed maintenance and gefitinib strategies. One recently published study of second-line treatment for advanced NSCLC showed 5-year QALYs of 0.279 and 0.269 and medical costs of $10,662.82 and $13,127.57 in the icotinib and gefitinib groups, respectively, suggesting that icotinib was a less expensive strategy than gefitinib [18]. Consistent with our study, that previous study also found that the utility of PFS was a sensitive parameter.…”
Section: Discussionsupporting
confidence: 91%
“…The rest 11 patients cannot be clearly distinguished based on histology appearance. Half of patients were subjected to icotinib treatment upon diagnosis largely because of its lower cost compared to the other two options [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the costs of those AEs were excluded from the total costs. AEs costs were derived from previous studies [23,24].…”
Section: Cost Estimatesmentioning
confidence: 99%